An Enhanced Clearly Frequency Yagi Antenna Technique Based On UHF - Bryan Wakita; Edy Sutejo; Amani Darma Tarigan (Jurnal Scientia, 2024)
The first thing that needs to be considered in designing an antenna is the frequency used. Frequency affects the size of the antenna. The smaller the antenna, the larger the dimensions of the antenna, and vice versa. The frequency used in this research is the UHF frequency (600 MHz). The antenna designed is a yagi antenna type which is based on this frequency so the size of the antenna is quite large. To be able to reduce the physical size of the antenna by maintaining or increasing the performance of the antenna, one technique that can be applied is the fractal Koch curve technique. From the antenna simulation results, the antenna characteristic parameters were obtained, namely gain of 12.9 dBi, VSWR 1.4, and unidirectional radiation pattern. After applying the fractal Koch Curve technique in iteration 1, an increase in gain of 7.3%, VSWR of 1.18, unidirectional radiation pattern and a decrease in the linear physical length of the antenna was obtained by 7.4%.